Decoding Black Women: Policing Practices and Rape Prosecution on the Streets of Philadelphia - Irving, Toni (NWSA Journal, 2008)
Black women are generally displaced as victims of rape. The police response to the sexual assault of black women in general and lower-class black women in particular is illustrative of how sexual ideologies help construct complex social hierarchies that in turn structure rights. How the law currently deals with rape places black women outside of the narrative frames that legitimate entitlement. Rape continues to stand in for, and effectively obscure, other social, political, and economic concerns. Unpublished and often ignored, the rape narrative is a ripe site to supply oppositional interpretations of national experience and transmit some of the structural problems in the criminal justice system. Pulling from over two thousand “real” rape cases of low-income black women ignored and not investigated in Philadelphia between 1995 and 2000, this article reads black female rape narratives as case studies in order to discuss the way personal narratives of rape victims are structured by competing and overwhelming sociolegal narratives that undercut their reception. As the fastest growing prison population, the presence of the law to punish black women stands in stark contrast to the absence of the law to protect them.
Keywords: 1900-1999; 1990-1999; afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; droit; droit des femmes* noires; droits des femmes*; féminisme afroaméricain; histoire et politique; intersectionnalité; inégalités; philadelphie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sex2283; sexisme; systèmes d'oppressions; thématiques; viol; violences; états-unis; études littéraires

Narrations déviantes : l'intimité entre femmes dans l'imaginaire français du dix-septième siècle - Legault, Marianne (Presses de l'Université Laval, 2008)
Si les rapports intimes entre les femmes ont toujours existé, comment expliquer leur absence dans le discours critique littéraire français malgré la foulée des études récentes sur les femmes, des études gays et lesbiennes et des études queers ? Voulant remédier à cette absence, ce livre retrace une généalogie de l’intimité féminine dans la littérature française du dix-septième siècle. Suivant une lecture qui s’inspire des études lesbiennes et queers, il explore l’effet d’un héritage androcentré sur l’intimité féminine au Grand Siècle, telle qu’elle a été envisagée par l’imaginaire d’Honoré d’Urfé dans L’Astrée et d’Isaac de Benserade dans Iphis et Iante. L’anxiété masculine qui se dégage de leurs représentations contraste avec la célébration de l’intimité féminine chez Madeleine de Scudéry dans Mathilde (d’Aguilar) et chez Charlotte-Rose de Caumont de La Force dans Plus belle que fée, deux œuvres qui élargissent les possibilités érotiques au sein des rapports intimes entre femmes au-delà de ce que les écrivaines avaient auparavant osé.
Keywords: 1600-1699; approches et analyses; arts; discipline; discours dominant; europe; france; identités LGBTQIA2+; patriarcat; personnes lesbiennes; périodes historiques; queer; régions géographiques; sexisme; systèmes d'oppressions; études littéraires

« Your Body is a Battleground » De quelques objets de l'histoire de l'art - Mader, Rachel; Schweizer, Nicole (Nouvelles Questions Féministes, 2005)
Notre article s'articule autour des points suivants: comment la critique féministe de histoire de l'art a-t-elle déplacé le ou les «objets» autour desquels s'articulait traditionnellement la discipline? Quels nouveaux «objets» ont dès lors été constitués? Et comment, à l'épreuve de ceux-ci, les histoires de l'art féministes doivent-elles, elles aussi, constamment se repositionner? L'exemple paradigmatique du corps dans la performance des années 70 nous permet d'interroger dans un deuxième temps la façon dont les artistes elles-mêmes ont déplacé la définition de l'objet, et par conséquent aussi celle du sujet - de l'œuvre comme de la perception.
Number: 1
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; artistes féministes; arts; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; performance; premier cycle; périodes historiques; représentation des femme*; ressource en ligne; sex2283; sexisme; systèmes d'oppressions; thématiques

Women making art: history, subjectivity, aesthetics - Meskimmon, Marsha.. (Routledge, 2003)
Women have been making art for centuries, yet their work has been seen as secondary or has gone unrecognized altogether. "Women making art" asks why this is so, and what it would take for us to realize the extent of women's extraordinary contribution to the arts. Marsha Meskimmon mobilizes contemporary feminist thinking to reconsider how and why women have made art. She examines work by a wide range of women artists fomr different cultures and historical periods, including Rebecca Horn, Rachel Whiteread, Shirin Neshat and Maya Lin, emphasizing the diversity of women's arts and the importance of differences between women.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; art contemporain; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Women in Dada: essays on sex, gender, and identity - Sawelson-Gorse, Naomi (The MIT Press, 2001)
Finally, a look at the role of women in the shaping of the high-spirited—but hardly feminist—Dada monement. For all of its iconoclasm, the Dada spirit was not without repression, and the Dada movement was not without misogynist tendencies. Indeed, the word Dada evokes the idea of the male—both as father and as domineering authority. Thus female colleagues were to be seen not heard, nurturers not usurpers, pleasant not disruptive.This book is the first to make the case that women's changing role in European and American society was critical to Dada. Debates about birth control and suffrage, a declining male population and expanding female workforce, the emergence of the New Woman, and Freudianism were among the forces that contributed to the Dadaist enterprise. Among the female dadaists discussed are the German émigré Baroness Elsa von Freytag-Loringhoven; Berlin dadaist Hannah Höch; French dadaists Juliette Roche and Suzanne Duchamp; Zurich dadaists Sophie Taeuber and Emmy Hennings; expatriate poet and artist Mina Loy; the "Queen of Greenwich Village," Clara Tice; Margaret Anderson and Jane Heap, the lesbian couple who ran The Little Review; and Beatrice Wood, who died in 1998 at the age of 105. The book also addresses issues of colonialist racism, cross-dressing and dandyism, and the gendering of the machine. The bibliography was compiled by the International Dada Archive (Timothy Shipe and Rudolf E. Kuenzli). Contributors Eleanor S. Apter, Barbara J. Bloemink, Willard Bohn, Carolyn Burke, William A. Camfield, Whitney Chadwick, Dorothea Dietrich, Susan Fillin-Yeh, Paul B. Franklin, Renée Riese Hubert, Marisa Januzzi, Amelia Jones, Marie T. Keller, Rudolf E. Kuenzli, Maud Lavin, Margaret A. Morgan, Dickran Tashjian, Elizabeth Hutton Turner, Barbara Zabel
Keywords: 1900-1999; 1910-1919; allemagne; amériques; approches et analyses; arts; cours; discipline; europe; femmes* artistes; france; har4600; histoire de l'art; histoire et politique; inégalités; premier cycle; périodes historiques; régions géographiques; sexisme; suisse; systèmes d'oppressions; thématiques; états-unis

Lesbian empire: Radical crosswriting in the Twenties - Wachman, Gay (Rutgers University Press, 2001)
Gay Wachman provides a critical new reading of sexually radical fiction by British women in the years during and after the First World War. She contrasts works by Sylvia Townsend Warner, Virginia Woolf, Rose Allatini, and Evadne Price with more politically and narratively conservative novels by Radclyffe Hall and Clemence Dane. These writers, she states, formed part of an alternative modernist tradition that functioned both within and against the repressive ideology of the British Empire, using fantasy as a means of reshaping and critiquing a world fragmented by war. Wachman places at the center of this tradition Sylvia Townsend Warner's achievement in undermining the inhibitions that faced women writing about forbidden love. She discusses Warner's use of crosswriting to transpose the otherwise unrepresentable lives of invisible lesbians into narratives about gay men, destabilizing the borders of race, class, and gender and challenging the codes of expression on which imperialist patriarchy and capitalism depended.
Keywords: amour interdit; approches et analyses; arts; discipline; europe; littérature; patriarcat; personnes lesbiennes; racisme; royaume-uni; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; transgression; études littéraires